Spin pairs in the Koronis asteroid family - Carruba, V. [UNESP]; Aljbaae, S.; Fazenda, L.; Barletta, W. [UNESP]; Lucchini, A. [UNESP]; Martins, B. [UNESP]; Furlaneto, P. [UNESP] (Elsevier, 2020)
Asteroid groups may either form because of collisions or the rotational failure of a parent body. Collisional asteroid families tend to be more spread in proper element domains, while young spin clusters are usually much more compact. Recently, it has been shown that young spin clusters may form at higher rates in extremely young asteroid families (families younger than ≃3 Myr) than in more evolved groups. Among asteroid families, the Koronis family is a natural laboratory to test this phenomenon. While the family itself is very evolved, with an estimated age of more than 2 Byr, two young sub-families are known to be located among Koronis members: the extremely young family of Karin, with an age of 5.75±0.05 Myr, and the relatively young sub-family of Koronis(2), with an age of 10±5 Myr. This fact allows studying the occurrence of young spin clusters in extremely young, young and evolved asteroid populations, all sharing the same physical properties. Using methods based on backward numerical integrations, we identify one possible pair candidate in the Karin family, and retrieved the pair 1741–258640 recently found in other works. No convincing spin pair candidate was found in the Koronis(2) sub-family. This suggests that the occurrence of young spin clusters in families older than ≃ 3 Myr may be a rarer event than what previously thought.
Keywords: Asteroids; Celestial mechanics; General; Individual; Koronis; Minor planets